Opening the fifth seal: Catholic martyrs and forces of religious competition - Rachel M. McCleary; Robert J. Barro (American Enterprise Institute (AEI), 2020)
Jorge Mario Bergoglio, since becoming Pope Francis in March 2013, is focusing on martyrdom in the Roman Catholic Church.
Keywords: A; 330; Catholic Church; competition; economics; Religion